Mechanically robust and tough waterborne polyurethane films based on diselenide bonds and dual H-bonding interactions with fast visible-light-triggered room-temperature self-healability. Issue 34 (28th July 2020) - Fan, Wuhou; Jin, Yong; Shi, Liangjie
Abstract : A dynamic but mechanically robust and tough polymer network was proposed, in which the fast room-temperature self-healing of our target polymer with mechanically robust and tough features is achieved under visible light. Abstract : Achieving the room-temperature self-healing of polymer materials with mechanically robust and tough features is a challenging project due to their conflicting attributes. Herein, a novel design concept of dynamic but mechanically robust and tough polymer networks was proposed derived from dynamic diselenide bonds and dual H-bonds, in which flexible fluorinated siloxane units and H-bonded urethane and urea groups are embedded simultaneously. Through adjustment of the mass fraction of fluorinated siloxane units incorporated, waterborne polyurethanes with good mechanical performances (tensile strength: 16.31 MPa; toughness: 69.8 MJ m −3 ) could be constructed. Meanwhile, this optimized sample could also be healed at room-temperature within 2 h under visible light. Therefore, the fast room-temperature self-healing of our elaborated polymers with mechanically robust and tough features is achieved, which has never been achieved for the contemporary polymer materials. The reconstruction of dual H-bonding interactions of urethane and urea moieties is responsible for the prophase healing after reconnecting the fracture surfaces, and macromolecular chains containing fluorinated siloxane units with excellent flexibility could promote the visible-light-triggered diselenide metathesis in a highly efficient manner subsequently. Moreover, much improved water resistance properties could also be achieved. The elaborated strategy will provide inspiration for developing mechanically robust and tough water-dispersed polymer materials with fast room-temperature self-repairing performance and desirable water resistance properties, which are of vital importance to the next generation of smart materials.